Respuesta :

Answer:

a=(x+7)(x+-2)

Step-by-step explanation:

(x+a)(x+b)=x²+(a+b)x+(ab)

Answer:

  a) (x +7)(x -2)

  b) x = -7 or +2

Step-by-step explanation:

a)

A trinomial is factored by realizing that the constant term (-14) is the product of the binomial constants, and the coefficient of the linear term (5) is their sum. Here, we can examine the factorization of -14 to see which factors may have a sum of 5:

  -14 = (-1)(14) = (-2)(7) = (-7)(2) = (-14)(1)

Sums of these factor pairs are 13, 5, -5, -13. Clearly, we could stop writing factorizations when the sum stops being positive. The values of interest are -7 and 2. They tell us the trinomial is factored as ...

  x² +5x -14 = (x +7)(x -2)

__

b)

The zeros of the quadratic are the values of x that make the above factors be zero. The zero product rule tells you the only way the product will be zero is for a factor to be zero.

  x +7 = 0   ⇒   x = -7

  x -2 = 0   ⇒   x = 2

The solutions are x = -7 or x = 2.

ACCESS MORE